Early meteorological records from Corrientes and Bahía Blanca, Argentina : initial ACRE-Argentina data rescue and related activities - Lakkis, Susan Gabriela (2022)
Fil: Lakkis, Susan Gabriela. Pontificia Universidad Católica Argentina. Facultad de Ingeniería y Ciencias Agrarias; Argentina